Surgical therapy of medullary thyroid cancer and our clinical experiences (Annals of Medical Research, 2021)
Aim: Medullary thyroid cancer (MTC) is a rare neuroendocrine tumor that originates from the thyroid parafollicular C cells and produces calcitonin. It is a quite aggressive disease with a potential to cause serious morbidity and mortality. In this study we aimed to report treatment outcomes of MTC, which has a bad prognosis and is difficult to manage.Material and Methods: The medical records of 1287 patients who were operated on for thyroid cancer between 2009 and 2018 were retrospectively assessed. Twenty-one patients (1.6%) were diagnosed with MTC. Results: Eleven (52.4%) patients were females. The age range of the patients was 54(14-85) years. Sixteen (76.2%) cases were sporadic and 5 (23.8%) were familial. Twelve patients underwent bilateral total thyroidectomy + central and unilateral neck dissection, 5(23.8%) bilateral total thyroidectomy + central and bilateral neck dissection, 4(19%) bilateral total thyroidectomy. Pathology examination revealed lymph node metastasis in 13(61.9%) patients. Three (14%) patients had simultaneous papillary thyroid cancer. Mean duration of follow-up was 52(3-96) months. Five (23.8%) patients suffered recurrence cervical lymph nodes (6 months later), lungs and bone metastasis (at 12th and 18th months), lungs (at 12thmonth), mediastinal lymph nodes (at 15th months), liver metastasis (at 6th months). Seven (33%) patients underwent chemo-radiotherapy. Conclusion: Surgery is the gold standard to control loco-regional disease and the only curative method among the available therapies in MTC treatment. Despite having a low incidence, MTC may still lead to serious mortality and morbidity in delayed cases and/or when loco-regional control cannot be achieved. Keywords: Medullary Thyroid Cancer; Surgery; Recurrence.
Keywords: Medullary Thyroid Cancer; Surgery; Recurrence.